(3eaJGM GdYdhes - (3GdScGcj , SQGL GdOjf CHh jYbhH jhSa Hf CHj HcQ Hf eMeO Hf Ydj GdScGcj GdNhGQRej GdMfaj, GdScGcj,J (B626 (3g` s ((3ESeGYjd Hf eMeO Hf YHO Gddg s)
(3ChdgG (B:s
(3bGd GdEeGe GdScGci s
(3BNQgG (B:s
(3heYQaI NhGUgG eeG jdRe UGMH Yde GdeYGai hGdHjGfJe s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B222 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B282s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1763s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdHdGZIs